The Development of Educational to Develop Out-of-School Children in The Situation of The Coronavirus (COVID-19) Epidemic in The Northern Region - Prasopsombat, Ladda (Journal of Graduate MCU KhonKaen Campus, 2022)
This research on the development of educational networks to develop out-of-school children in the situation of the coronavirus (COVID-19) epidemic in the northern region aimed to 1. Provide out-of-school children and youth to receive appropriate care in the coronavirus (COVID-19) epidemic situation and have the opportunity to learn according to their potential and needs. 2 Enhance the potential of out-of-school children and youth to have knowledge and ability to learn with quality. 3. Develop learning networks and development of learning quality and quality of life of out-of-school children and youth. This study selected a target group of 6 organizations working on out-of-school children and youth in the northern region by using qualitative data collection methods from interviews with teachers, staff from local organizations, community leaders, and other stakeholders. The results of the study discovered 3 methods to help out-of-school children and youth which are: 1. creating a database of names and needs of out-of-school children and youth. 2. Creating a database of community leaders, teachers, child caregivers, wisdom teachers, village scholars to jointly develop potential, follow up, support target groups. 3. Finding a way to help, monitor, support, and develop the potential of out-of-school children and youth that are consistent with the ne eds and appropriateness of each area. This creates a model of support and assistance for out-of-school children and youth with three skills: life skills, vocational skills, and educational skills including the establishment of 5 community learning centers.